2015
DOI: 10.1111/bjd.13508
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy and risk factors for predicting metastasis in cutaneous squamous cell carcinoma

Abstract: Patients with risk factors (cSCC with a tumour thickness > 4 mm or recurrent disease) may develop metastases within the first 2 years despite a negative SLNB. Therefore these patients should be closely monitored during the follow-up. Based on our data SLNB does not provide diagnostic value for patients with cSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 31 publications
2
46
0
5
Order By: Relevance
“…A review of all case series reporting SLNB in cSCC is detailed in Table IV. 13,18,28,[41][42][43][44][45][46][47][48][49][50][51][52] Our systematic review identified an overall positive rate for SLNB of 13.9% (32 of 231 patients) and a false-negative rate of 4.6% (10 of 215 patients) in cSCC. The authors usually stated that patients had high-risk factors for lymph node involvement.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of all case series reporting SLNB in cSCC is detailed in Table IV. 13,18,28,[41][42][43][44][45][46][47][48][49][50][51][52] Our systematic review identified an overall positive rate for SLNB of 13.9% (32 of 231 patients) and a false-negative rate of 4.6% (10 of 215 patients) in cSCC. The authors usually stated that patients had high-risk factors for lymph node involvement.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…52 As the available data are limited, extrapolating from other malignancies where SLNB is performed routinely may aid us in addressing our question indirectly, ie, in melanoma, breast cancer, and head and neck SCC, among others. SLNB in these patients has an important staging role and identifies patients who could benefit from regional treatment.…”
Section: Does Slnb Improve Survival and Other Outcomes In Cscc?mentioning
confidence: 99%
“…Although immunosuppression was associated with recurrence in the prospective data by Brantsch et al 4 and in certain subsets of well-defined patients, such as those with chronic lymphocytic leukemia, 23 the results of these 2 studies were likely offset by other reports that did not stratify on the basis of the type of immunosuppression. 6,34,39 Taken together, the data suggest that clarification of the nature of the immunosuppression is critical for understanding the factors that influence local recurrence. Notably, the I 2 for location on the lip or the ear and for immunosuppression were increased at 52%, 59%, and 39%, respectively, indicating substantial data inconsistency, which also could contribute to a lack of statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…Tumor location on the temple, although not part of the AJCC, UICC, or BWH staging system, 44 was associated with a higher risk of recurrence (RR [95% CI], 3.20 [1.1–9.0]; P =.03) than tumor location on either lip or ear, albeit this finding was based on a single, but relatively large, retrospective analysis by Schmults et al 8 Poor differentiation also was found to have statistically significant association with recurrence (RR [95% CI], 2.66 [1.72–4.14]; P <.01), based on pooled data from 11 studies. 4,6,17,19,2224,34,37,39,41 …”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, em casos de câncer de mama não existe associação entre a presença de linfonodos axilares clinicamente positivos e o desenvolvimento de tumores metastáticos 19 . Já Krediet et al (2015) 20 , observaram que alguns pacientes com CEC em pele chegaram a desenvolver tumores metastáticos, apesar de apresentarem linfonodos negativos, sugerindo que nem sempre esse fator pode ser associado com um bom prognóstico em CEC cutâneo. Essa discussão é ampla, devido às características particulares do comportamento biológico de cada tipo de câncer e a metodologia empregada por cada autor.…”
unclassified